2022
DOI: 10.1088/1755-1315/989/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of coastline changes of maruni beach in Manokwari during 1995-2021 period

Abstract: The coastal area of Maruni at Manokwari Regency is known for its potential as a fish-producing area, industry, settlements, ports, and others. However, some parts of Maruni coastal areas have been damaged due to the development. The coastal area experienced changes caused by both natural processes and human activities. The presence of natural and artificial processes in coastal areas results in accretion and abrasion. The dynamics of oceanographic pressures such as sea tidal, sea waves, ocean currents, and tid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Sloping coastal slopes tend to have large high tide limits. These conditions indicated that the tidal area (coastal line) in Andai was under high pressure due to waves and tidal currents (Tapilatu et al 2022), so the sediment in the vicinity was eroded and displaced. It was indicated by the grain size of the sediments found to be more varied, including gravel, sandy, and muddy sand.…”
Section: Microplastic Distribution Vs Coastal Slopementioning
confidence: 99%
“…Sloping coastal slopes tend to have large high tide limits. These conditions indicated that the tidal area (coastal line) in Andai was under high pressure due to waves and tidal currents (Tapilatu et al 2022), so the sediment in the vicinity was eroded and displaced. It was indicated by the grain size of the sediments found to be more varied, including gravel, sandy, and muddy sand.…”
Section: Microplastic Distribution Vs Coastal Slopementioning
confidence: 99%